Long-term high-altitude exposure influences task-related representations in visual working memory - Bao, Xiaohua; Zhang, Delong; Li, Xiaoyan; Liu, Ming; Ma, Hailin (Frontiers in Neurology, 2023)
Human working memory is impaired when individuals are exposed to high altitudes, however, whether the capacity of visual working memory is affected remains unclear. This study combined a lateralized change detection task and event-related potentials analysis to explore changes in visual working memory capacity among individuals who emigrated from a low-altitude environment to Tibet (a high-altitude environment). We measured participants' contralateral delay activity (CDA) under different memory loads. ERP component analysis showed that both the high-altitude and low-altitude groups reached an asymptote at memory load four. However, the high-altitude group performed larger ipsilateral activity than contralateral activity under each memory load, compared with the low-altitude group. These findings demonstrated that the attentional resource of long-term HA exposure is more captured by task-irrelevant information, potentially due to impaired inhibitory control, which makes it difficult for them to exclude the interference of task-irrelevant information.